Strategies for rural development: Results of the FAO World Conference - Johannes Dohnanyi (Intereconomics, 1979)
The “World Conference on Agrarian Reform and Rural Development” (WCARRD), which was held from July 12–20 at the headquarters of the Food and Agriculture Organization of the United Nations (FAO) in Rome, tried to set up new targets for urgent national and international efforts to overcome the obviously desperate situation of the rural poor in the developing countries. What were the results of the conference?
Keywords: 330